DDX17 promotes DENV-2 replication via interaction with viral dsRNA and G3BP1 - Peijun Han; Wei Ye; Hongwei Ma; Yangchao Dong; Xin Lv; He Liu; Linfeng Cheng; Liang Zhang; Sumin Li; Yingfeng Lei; Fanglin Zhang (International Journal of Medical Microbiology)
Dengue virus (DENV) is one of the major arboviruses that pose a serious threat to global human health. However, there is currently no specific antiviral drug available for the treatment of DENV infection. DDX17, a member of the DExD/H-box helicase family, has been implicated in the replication processes of various viruses. Our research group discovered that during the early stages of dengue virus replication, DDX17 promotes viral replication and suppresses the activity of the IFN promoter. Furthermore, DDX17 binds to viral dsRNA and interacts with G3BP1, a component of stress granules (SGs), to inhibit SG formation, thereby enhancing viral replication. By elucidating the role of DDX17 in the early stages of dengue virus replication, our findings provide valuable insights into host-pathogen interactions during DENV infection, offering potential therapeutic perspectives.